Utilization Of Kahoot Game-Based Learning Media for Vocational School 6 Bengkulu City - Islamy, Muhammad Fajry; Asnawati, Asnawati; Siska, Jumiati (CV. Media Inti Teknologi, 2024)
The purpose of this study was to determine how Kahoot is used as a learning medium at SMK N 6 Kota Bengkulu in Vocational Subjects. The research method used is qualitative. The subjects of the study were Class XI TKJ. Data collection techniques used were observation, interviews, questionnaires, and documentation. Based on the data obtained from the results of the study, both obtained from the results of observations, interviews, filling out student response questionnaires, and documentation with class 80, % of students think that Kahoot game-based learning media is useful for students, and students who were interviewed also know about Kahoot and think that the Kahoot application is a fun application to use in the learning process. Utilization of Kahoot game-based learning media, especially in Vocational subjects at SMK Negeri 6, Bengkulu City. For students, using Kahoot media is more fun than having to write questions and answers in a notebook.